MATEMATIKA DALAM BUDAYA PAGARALAM - Chika Rahayu; Somakim Somakim; Yusuf Hartono (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
Pagaralam is a major tourist destination in the area of South Sumatera Province, Indonesia. In addition to having a beautifulÂ  nature, the air is so cool, there is something very interesting to study the culture. Pagaralam has a culture potenstial based on mathematics. This article contains an overview of the relationship between mathematics and Pagaralam culture, in terms of the time division and division system. The existence of several customs or customs has been carried out continously in the culture of society without realizing it is an idea related to mathematics known as ethnomathematics. Matematics learning in school using cultural contexts can lead to the interest and curiousity of learners to learn math and can help learners to achieve a character education as well as to continue a good culture to the next generation and motivate learners to connect math to the real world.